2016
DOI: 10.1177/0961000616667802
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of information literacy skills among first-year postgraduate students at Sokoine University of Agriculture Tanzania

Abstract: This study was set to examine and identify some aspects of information literacy skills among postgraduate students at Sokoine University of Agriculture and determine challenges and problems facing them in terms of searching and use of various information resources. Systematic probability sampling and questionnaires were used to collect data from175 students out of 314 first-year postgraduate students registered. The findings showed that although information literacy exists among students, a good number of stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 20 publications
(20 reference statements)
0
14
0
1
Order By: Relevance
“…McDonald (2015) also urged librarians to embrace technology actively and play a dominant role in their social, academic and professional fields. Therefore, Chiu and Chou, 2012;Lwehabura, 2018 andBekker et al (2015) suggested digital fabrication and reflectors designed-based learning (RDBL) improving the young generation social activities, skills, and practices in the basic data structure. Even communication technology has changed the academic library from manual to automation and digital database access.…”
Section: Literature Reviewmentioning
confidence: 99%
“…McDonald (2015) also urged librarians to embrace technology actively and play a dominant role in their social, academic and professional fields. Therefore, Chiu and Chou, 2012;Lwehabura, 2018 andBekker et al (2015) suggested digital fabrication and reflectors designed-based learning (RDBL) improving the young generation social activities, skills, and practices in the basic data structure. Even communication technology has changed the academic library from manual to automation and digital database access.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There is also a lack of a broader understanding of the links between information literacy and society or the transition to university (Lanning & Mallek, 2017;Lwehabura, 2018;Salisbury & Karasmanis, 2011), which is understandable to respondents. However, the generational emphasis is interesting (Eriksson-Backa et al, 2012;Lu et al, 2016;Strong et al, 2012) and the very perceived importance of information literacy present in students.…”
Section: Discussionmentioning
confidence: 99%
“…Proto je nezbytné, aby na tuto situaci reagovaly také univerzity a hledaly cesty k podpoře studentů, kteří se ve vysokoškolském prostředí mohou cítit ztraceni. Svět infomačních potřeb je totiž radikálně odlišný (Salisbury & Karasmanis, 2011;Lwehabura, 2018;Schofield, 2012;Farmer, 2015;Lanning & Mallek, 2017), takže zatímco na střední škole se informační gramotnost silně zaměřuje na oblast médií a sociálních sítí v kontextu vysoké školy lze vidět důraz na odborné zdroje a vědecké časopisy, práce s databázemi a především na náročnější operace jako jsou pokročilé vyhledávací strategie schopnost pracovat s daty a kriticky hodnotit jednotlivé texty (Donham, 2014;Head, 2013). Zatímco Candy (2004) se domníval, že je možné pracovat s různou úrovní informační gramotnost, jako s něčím přirozeným, protože jde o kompetenci stejnou, jako mnoho dalších, zdá se, že výzkumný diskurs je v tomto ohledu velice odlišný.…”
Section: Diskuseunclassified